Material and process engineering challenges in Ge-rich GST for embedded PCM. (January 2022) - Redaelli, Andrea; Petroni, Elisa; Annunziata, Roberto
Abstract: Phase-Change Memory (PCM) is one of the most recent technologies to enter the embedded memory market for consumer- and automotive-grade applications. However, conventional PCM materials cannot be used for certain applications due to the severe temperature constraints of the soldering specifications required by consumer-grade electronics and the demanding mission profiles of automotive components. To comply with these requirements, researchers have been developing innovative solutions to ensure that the active materials in PCM devices can work in such harsh conditions. In this paper, a review of the main steps of this path will be proposed, first following the evolution of the PCM technology, and then focusing on the material optimization itself. Challenges of actual embedded PCM will be also discussed and an outlook for future developments provided.